Implementation of resource-saving technologies of whey processing - a step to sustainable development of dairy companies - Mykhalevych, Artur; Sapiga, Victoria; Bandura (Kuzmyk), Uliana (My University, 2021)
The implementation of resource-saving technologies involves the development of industries, including their greening, which ensures the full and integrated use of raw materials and significantly reduces the negative impact of industrial waste on the natural environment.
Keywords: resource-saving technologies; whey; dairy companies; ресурсозберігаючі технології; сироватка; молочні компанії; кафедра технології молока і молочних продуктів